The Determinants of Investment Decision on High-Risk Asset: A Cross-Generational Perspective - Isnaini Nuzula Agustin; Jefri Ariffendi; Novita Ratna Satiti; Ria Karina (Penerbit Goodwood, 2026)
Purpose: This study investigates the determinants of investment decisions in high-risk assets across generational cohorts in Indonesia, focusing on the roles of overconfidence and gambler’s fallacy. Methodology: Using survey data from 340 individual investors, Partial Least Squares-Structural Equation Modeling (PLS-SEM) was employed to examine direct and mediating relationships, including cross-generational comparisons. Results: The results indicate that overconfidence and gambler’s fallacy significantly increase risk propensity while reducing financial literacy, both of which subsequently influence investment decisions. Risk propensity serves as a positive mediator, whereas financial literacy functions as a negative mediator, suggesting that cognitive biases may weaken the rational application of financial knowledge to gambling decisions. Cross-generational differences were also observed, with varying relationship strengths across the age groups. Conclusions: This study concludes that behavioral biases are critical determinants of investment decisions in high-risk assets among Indonesian investors, whereby younger generations tend to be more influenced by heuristic-driven biases in digital investment environments, whereas older generations display more experience-based decision patterns. Limitations: This study is limited by its focus on Indonesian investors, which may reduce generalizability across broader contexts, and its reliance on self-reported data and cross-sectional design. Contributions: By integrating Prospect Theory, the Theory of Planned Behavior, and Human Capital Theory in an emerging market context, this study contributes to the behavioral finance literature by identifying the dual and asymmetric mediating roles of risk propensity and financial literacy in shaping investment decisions across generations.